2022
DOI: 10.3389/fmed.2022.833996
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Platelet Levels and 28-Day Mortality in Patients With Sepsis: A Retrospective Analysis of a Large Clinical Database MIMIC-IV

Abstract: BackgroundThis research focused on evaluating the correlation between platelet count and sepsis prognosis, and even the dose-response relationship, in a cohort of American adults.MethodPlatelet counts were recorded retrospectively after hospitalization for patients admitted to Beth Israel Deaconess Medical Center’s intensive care unit between 2008 and 2019. On admission to the intensive care unit, sepsis patients were divided into four categories based on platelet counts (very low < 50 × 109/L, intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…Whereas the PESI and sPESI demonstrated the same limitations in our two unselected cohorts, PATHOS score is based on fundamental and easily available items used to assess circulatory shock, pulmonary dysfunction, acute cardiac damage, and platelet count (the latter being an independent predictor of IHM in more conditions than just PE). 8,[28][29][30] According to our results, the positive overall NRIs in the comparisons between PATHOS and PESI and PATHOS and sPESI confirm that PATHOS has better discrimination accuracy than the older measures, showing that a net percentage of 31% (PATHOS vs. PESI) and 29% (PATHOS vs. sPESI) of patients without IHM were correctly reclassified by the new measure. Thus, compared with the other two scores, PATHOS has a higher ability to estimate patients at low risk for IHM than the PESI and sPESI.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Whereas the PESI and sPESI demonstrated the same limitations in our two unselected cohorts, PATHOS score is based on fundamental and easily available items used to assess circulatory shock, pulmonary dysfunction, acute cardiac damage, and platelet count (the latter being an independent predictor of IHM in more conditions than just PE). 8,[28][29][30] According to our results, the positive overall NRIs in the comparisons between PATHOS and PESI and PATHOS and sPESI confirm that PATHOS has better discrimination accuracy than the older measures, showing that a net percentage of 31% (PATHOS vs. PESI) and 29% (PATHOS vs. sPESI) of patients without IHM were correctly reclassified by the new measure. Thus, compared with the other two scores, PATHOS has a higher ability to estimate patients at low risk for IHM than the PESI and sPESI.…”
Section: Discussionsupporting
confidence: 69%
“…Notably, our two cohorts are very different in terms of demographic and clinical characteristics due to their different locations and resident populations, so they reflect the actual variety of patients and the need for a simple and effective score in an emergency setting. Whereas the PESI and sPESI demonstrated the same limitations in our two unselected cohorts, PATHOS score is based on fundamental and easily available items used to assess circulatory shock, pulmonary dysfunction, acute cardiac damage, and platelet count (the latter being an independent predictor of IHM in more conditions than just PE) [ 8 , 28 30 ]. According to our results, the positive overall NRIs in the comparisons between PATHOS and PESI and PATHOS and sPESI confirm that PATHOS has better discrimination accuracy than the older measures, showing that a net percentage of 31% (PATHOS vs. PESI) and 29% (PATHOS vs. sPESI) of patients without IHM were correctly reclassified by the new measure.…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19 patients, platelets coordinate with neutrophils to release NETs, which can induce platelet-neutrophil aggregates with thrombocytopenia ( 38 , 39 ). These can activate the procoagulant cascade, which is associated with the prognosis of septic death and microvascular thrombosis and subsequent organ dysfunction ( 40 , 41 ). Consistent with our findings, a recent study from Thailand found that PWR can be an accurate predictor of in-hospital mortality in patients with severe COVID-19 pneumonia ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…As platelet count is a simple, cheap, and easily available biomarker and has been independently associated with disease severity and mortality risk in intensive care unit (ICU) H5 (40)(41)(42) , it has been rapidly adopted as a potential biomarker for COVID-19 patients. The number of platelets was reported to be significantly reduced in COVID-19 patients (43,44) 49) The previous meta-analysis reported that platelets were not an appropriate marker for considering the severity of COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%